[Ag20S2P(OR)212]: A Superatom Complex with a Chiral Metallic Core and High Potential for Isomerism. Issue 29 (8th June 2016) - Dhayal, Rajendra S.; Lin, Yan‐Ru; Liao, Jian‐Hong; Chen, Yuan‐Jang; Liu, Yu‐Chiao; Chiang, Ming‐Hsi; Kahlal, Samia; Saillard, Jean‐Yves; Liu, C. W.
Abstract: The synthesis and structural determination of a silver nanocluster [Ag20 S2 P(O i Pr)2 12 ] (2 ), which contains an intrinsic chiral metallic core, is produced by reduction of one silver ion from the eight‐electron superatom complex [Ag21 S2 P(O i Pr)2 12 ](PF6 ) (1 ) by borohydrides. Single‐crystal X‐ray analysis displays an Ag20 core of pseudo C 3 symmetry comprising a silver‐centered Ag13 icosahedron capped by seven silver atoms. Its n ‐propyl derivative, [Ag20 S2 P(O n Pr)2 12 ] (3 ), can also be prepared by the treatment of silver(I) salts and dithiophosphates in a stoichiometric ratio in the presence of excess amount of [BH4 ] − . Crystal structure analyses reveal that the capping silver‐atom positions relative to their icosahedral core are distinctly different in2 and3 and generate isomeric, chiral Ag20 cores. Both Ag20 clusters display an emission maximum in the near IR region. DFT calculations are consistent with a description within the superatom model of an 8‐electron [Ag13 ] 5+ core protected by a [Ag7 S2 P(OR)2 12 ] 5− external shell. Two additional structural variations are predicted by DFT, showing the potential for isomerism in such [Ag20 S2 P(OR)2 12 ] species. Abstract : Chiral silver nanocluster : The structure of an intrinsically chiral Ag20 nanocluster was determinded. Containing a silver‐centered icosahedron capped by seven silver atoms, it was rationalized to be an eight‐electron superatom complex. Isomeric Ag20 cores with distinct symmetry were characterized in two derivatives ( n Pr C 1 ; i Pr C 3 ). DFT was used to predict the presence of additional structural variations to show rich isomerism in the Ag20 metallic core.